Investigation on the dynamics of Z-pinch in discharge-produced plasma sources via two-dimensional MHD simulations - Yanxia Xu; Make Ying; Xuanyu Yuanhua; Jianhui Zhou; Xiaoqiang Zhang; Guanxin Huang; Benkun Lv; Haonan Zhang; Jiangwei Li; Zongqiang Yu; Yang Yang; Yue Cheng; et al. (AIP Advances)
The plasma Z-pinch plays a pivotal role in generating bright optical radiation with short wavelengths in Discharge-produced Plasma (DPP) sources, such as capillary discharge-produced and inductively driven electrodeless light sources. In this study, we investigate the Z-pinch dynamics of DPP-based electrodeless light sources using two-dimensional magnetohydrodynamic simulations via the USim code. Meanwhile, the influences of plasma density disturbances and the parametric effects of pulsed current on the Z-pinch process are examined and discussed. The results reveal that in the absence of density disturbances, the interplay between magnetic and kinetic pressures drives a stable, periodic Z-pinch behavior accompanied by a recurring “bouncing” effect, which is closely associated with the properties of the current pulse. Specifically, a higher peak current and narrower pulse width result in more frequent pinching events and “bouncing” cycles, leading to enhanced pinching amplitude, plasma density, temperature, and kinetic energy density. However, the introduction of initial density disturbances brings about Magneto-Rayleigh–Taylor (MRT) instability, resulting in the deformation of cylindrical symmetry and earlier termination of Z-pinch processes. Moreover, it is also observed that an increase in disturbance amplitude, as well as the pulse width, exacerbates the evolution of MRT instability, thereby reducing the efficiency and longevity of the Z-pinch process.